COMMITMENT, MOTIVATION, LEADERSHIP AND WORK CULTURE ON JOB SATISFACTION AND TEACHER PERFORMANCE AT SMK MULTI MEKANIK MASMUR PEKANBARU - Aulia Ramadona; Rizaldi Putra; Dadi Komardi (Journal of Applied Business and Technology, 2021)
The purpose of this study was to examine the effect of analysis of commitment, motivation, and leadership and work culture on job satisfaction and teacher performance at SMK Multi Mekanik Masmur Pekanbaru. The sampling technique used in this research is purposive sampling. The sampling criteria in this study were all educators at the Masmur Multi-Mechanical School. There are 100 teachers in this school. The remaining 20 people are education personnel. So the respondents in this study were 100 people who were all education personnel. Data collection techniques using a questionnaire (questionnaire), interviews and documentation. The data analysis technique used descriptive analysis and hypothesis analysis using SPSS and SEM PLS analysis. The results obtained indicate that there is an insignificant effect of commitment on job satisfaction, motivation has no significant effect on job satisfaction, leadership has no significant effect on job satisfaction and work culture has a significant effect on job satisfaction. Furthermore, commitment has no significant effect on teacher performance, motivation has no significant effect on teacher performance, leadership has no significant effect on teacher performance, work culture has a significant effect on teacher performance, and job satisfaction has a significant effect on teacher performance.